PELAKSANAAN SUPERVISI AKADEMIK KEPALA SEKOLAH DI SMA NEGERI 3 MERANGIN - Rahmayanti Chaidir; Novi Susanti; Sumarni Umar Ahmad; Aprianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Academic supervision is an important function of school leadership in improving teacher professionalism and the quality of learning. This study aims to analyze the implementation of academic supervision by the principal at SMA Negeri 3 Merangin, focusing on the supervision model, the application of supervision principles, implementation constraints, and its impact on teacher professionalism. This study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, while data validity was strengthened through technical triangulation. The results showed that academic supervision had been implemented according to a planned schedule through planning, pre-observation, classroom observation, post-observation, and documentation stages. However, its implementation was still predominantly conventional and administrative, particularly focusing on the completeness of learning administration. The scientific principle was reflected in the use of structured supervision instruments, while democratic, cooperative, and constructive principles had not been optimally implemented. The main obstacles included the principal's limited time, insufficient coaching skills, resistance from some teachers, and supervision instruments that were not sufficiently responsive to contemporary learning needs. The impact of supervision was more evident in improving teachers' compliance with learning administration than in producing substantial changes in teaching practices and reflective professional culture. The study concludes that academic supervision needs to shift from administrative inspection toward collaborative, constructive, and coaching-oriented professional development.